Talent development abroad. Young football players` experiences and challenges on being recruited to English academies - Hem, M.; Fuhre, J.; Høigaard, R.; Sæther, S. A. (Soccer & Society, 2022)
The aim of the current study was to gain insight into talented Norwegian football players who made a club transfer to an English football academy, by investigating the players` choice of academy, main challenges upon arrival, how they settled in both athletically and socially and their day-to-day life in the academy. Eight Norwegian players registered in an English professional football academy between the ages of 16 and 18 years were interviewed in retrospect. The challenges that the players met were mostly related to their efforts to develop as players, such as going into an extremely high-performance environment, which was quite different from what they perceived in their original club. Even though the transfer to an English professional club seemed like the natural choice to make, the players experienced a cultural shock not just athletically, but also socially and emotionally in their everyday life in a host family.